2019
DOI: 10.1088/1674-1056/28/2/024205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermally induced birefringence on high power picosecond azimuthal polarization Nd:YAG laser system

Abstract: Pulse-burst 1064-nm picosecond azimuthal polarization beam amplification up to an average power of 16.32 W using side-pumped Nd: YAG amplifiers has been demonstrated. The maximum envelop energy as much as 16.32 mJ, corresponding to a power amplification factor of 299.5%. A simple criterion was defined to help estimate the amount of depolarization in Nd:YAG amplifier stages. The degree of depolarization of the beam was 7.1% and the beam quality was measured to be M 2 = 3.69. The reason for the azimuthal polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…And the experimentally measured thermal focal length value is greater than 3 m. Combined with the measured thermal focal length value and theoretical analyses of laser cavity mode, it can be concluded that the marked ranges a and b correspond to the power-stable region and mode-stable region within LEDpumped CW solid-state laser's optimal working stability zone, while the marked mode-stable region c and power-stable region d within the traditional LD-pumped CW solid-state laser are optima work stability zone. [19][20][21][22][23][24][25]25] Due to the thermal accumulation from LED CW pumping, the temperature difference between the crystal's interior and thermal distortion gradually increase, resulting in a transition from range a to range b in the laser stable area. Moreover, the value of thermal focal length gradually becomes smaller, and the value of the fundamental mode spot radius ω 0 and mode volume also decreases accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…And the experimentally measured thermal focal length value is greater than 3 m. Combined with the measured thermal focal length value and theoretical analyses of laser cavity mode, it can be concluded that the marked ranges a and b correspond to the power-stable region and mode-stable region within LEDpumped CW solid-state laser's optimal working stability zone, while the marked mode-stable region c and power-stable region d within the traditional LD-pumped CW solid-state laser are optima work stability zone. [19][20][21][22][23][24][25]25] Due to the thermal accumulation from LED CW pumping, the temperature difference between the crystal's interior and thermal distortion gradually increase, resulting in a transition from range a to range b in the laser stable area. Moreover, the value of thermal focal length gradually becomes smaller, and the value of the fundamental mode spot radius ω 0 and mode volume also decreases accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the power density in the crystal was low, and the overlap between TEM00 and LED pump modes was deviated. [10][11][12][13][14][15] Thus, to capture more emission from the LED to enhance the coupling efficiency and enable higher mode matching, it was necessary to modify the LED emission mechanism, optimize the pump structure and increase the area fill factor to achieve a higher-efficiency LED pump laser. In this work, we analyze the emission mechanism of LEDs and address the coupling efficiency of LED-pumped lasers using non-diffuse scattering LEDs to rationalize the five-way pumping structure of LEDs.…”
mentioning
confidence: 99%